2001
DOI: 10.1109/22.903109
|View full text |Cite
|
Sign up to set email alerts
|

A novel interpretation of transistor S-parameters by poles and zeros for RF IC circuit design

Abstract: In this paper, we have developed an interpretation of transistor S-parameters by poles and zeros. The results from our proposed method agreed well with experimental data from GaAs FETs and Si MOSFET's. The concept of source-series feedback was employed to analyze a transistor circuit set up for the measurement of the S-parameters. Our method can describe the frequency responses of all transistor S-parameters very easily and the calculated S-parameters are scalable with device sizes. It was also found that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
29
0

Year Published

2003
2003
2004
2004

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 4 publications
0
29
0
Order By: Relevance
“…Up to now, two different origins of the S 22 kink phenomenon in deep sub-micron RF MOSFETs have been reported [5][6]. Hjelmgren, et al attributed the phenomenon to the small signal-substrate resistance [5], while Lu, et al concluded that it resulted from the transconductance and, consequently, the size of the transistor [6].…”
Section: Introductionmentioning
confidence: 96%
See 4 more Smart Citations
“…Up to now, two different origins of the S 22 kink phenomenon in deep sub-micron RF MOSFETs have been reported [5][6]. Hjelmgren, et al attributed the phenomenon to the small signal-substrate resistance [5], while Lu, et al concluded that it resulted from the transconductance and, consequently, the size of the transistor [6].…”
Section: Introductionmentioning
confidence: 96%
“…A comparable full wave simulation using Ansoft's HFSS requires more than 100 hours to accurately model the frequency domain behavior of the whole structure. [6]. In this paper, based on the results of RF power n-MOSFETs for system on chip (SOC) applications, the third origin of the S 22 kink phenomenon in deep sub-micron RF MOSFETs, that is, small-signal gate-drain resistance, is reported and explained quantitatively for the first time.…”
mentioning
confidence: 97%
See 3 more Smart Citations